Neural Representation Enhanced for Speech and Reduced for Background Noise With a Hearing Aid Noise Reduction Scheme During a Selective Attention Task - Alickovic, Emina; Lunner, Thomas; Wendt, Dorothea; Fiedler, Lorenz; Hietkamp, Renskje; Ng, Elaine Hoi Ning; Graversen, Carina (Frontiers in Neuroscience, 2020)
Selectively attending to a target talker while ignoring multiple interferers is more difficult for hearing impaired individuals compared to their normal-hearing peers, and becomes more difficult with increased background noise levels. To overcome such difficulties, hearing aids offer noise reduction schemes. Here we aimed to investigate the effect of noise reduction processing on the neural representation of speech envelopes across two different background noise levels by using a stimulus reconstruction method. The electroencephalogram (EEG) was recorded while twenty-two hearing impaired participants fitted with hearing aids were performing a listening task. Participants were instructed to listen to a target talker in front while ignoring a competing talker also in front in the presence of multi-talker background babble noise. Measures of neural representation for the envelopes of the attended speech, unattended speech, and the background noise were calculated separately. The results show that the neural representation of the attended speech envelope was enhanced by the active noise reduction scheme for both background noise levels. The neural representation of the attended speech envelope at the low SNR was shifted approximately by 5 dB toward the higher when the noise reduction scheme was activated. The neural representation of the ignored speech envelope was modulated by the noise reduction scheme and was mostly enhanced in the conditions with more background noise. The neural representation of the background noise was modulated by the noise reduction scheme and was significantly reduced in the conditions with more background noise. The neural representation of the net sum of the ignored acoustic scene (ignored talker and background babble) was not modulated by noise reduction scheme but was significantly reduced in the conditions with the reduced level of background noise. We conclude that the active noise reduction scheme enhanced the neural representation of both the attended and ignored speakers, and reduced the neural representation of background noise, while the net sum of the ignored acoustic scene was not enhanced. We contend that these results provide a neural index that could be useful for assessing the effects of hearing aids on auditory and cognitive processing in hearing impaired populations.